Prospecção e caracterização de vírus zoonóticos em remanescentes florestais inseridos em matrizes urbanas: implicações para o conhecimento da dinâmica ecológica e evolutiva - Ana Gabriella Stoffella Dutra (2023)
Emerging infectious diseases (EID) are a public health worldwide problem. In this scenario, zoonoses account for the majority of emergency events, and viruses represent the second largest cause of EID. Brazil is considered a “hotspot” for emerging pathogens, and in the epidemiological scenario has the occurrence of important viruses with a relevant impact on public health, such as arboviral diseases, caused by the ZIKV, YFV, DENV and CHIKV viruses, as well as Bovine Vaccinia (VACV), in addition to the SARS-CoV-2, responsible for the COVID-19 pandemic. In this context, the aim of this study was to investigate and characterize zoonotic viruses circulating in small wild mammals living in forest remnants located in Belo Horizonte, MG. Molecular investigation of these viruses in organs of wild rodents and marsupials demonstrated the absence of arbovirus circulation in these animals. For VACV investigation, a nucleotide sequence of the A56R gene was obtained from a rodent sample (Cerradomys spp.), the molecular investigation also showed possible viral circulation in a marsupial (Marmosops incanus). Our findings raise questions about the possible role of these mammals in the maintenance and transmission cycles of these viruses in green areas inserted in urban environments. The data presented here also confirmed the circulation of SARS-CoV-2 in coatis (Nasua nasua), suggesting the occurrence of viral spillback events in local sylvatic mammals during the pandemic. The occurrence of natural SARS-CoV-2 infection in coatis by the zeta variant (P.2) was confirmed by complete genome sequencing and phylogenetic inferences. Furthermore, the serological investigation showed that 50% of the analyzed coatis had anti-SARS-CoV-2 neutralizing antibodies. Considering the molecular investigation of arboviruses, none of the coatis was positive. Detection of VACV was not confirmed by qPCR, and no anti-OPV antibodies were detected in the sera of the tested coatis. The monitoring of zoonotic viruses in small mammals located in urban-sylvatic interface areas contributes to elucidate the transmission dynamics of these viruses. In addition, understanding the enzootic cycles of these viruses helps to support control and prevention measures in the face of emergency events. Furthermore, the borderline occurrence in urban areas indicates the risk of human exposure to zoonotic infections.